Enantioselective Functionalization of Terminal Alkynes by Gold Catalysis - Mourad, Asmaa Kamal; Czekelius, Constantin (Synlett, 2013)
The enantioselective functionalization of alkynes is still a challenge in the field of gold catalysis. This article describes recent progress in the application of gold complexes with optically active ligands or counteranions for activation of alkynes towards nucleophiles, including the recently reported desymmetrization of terminal diynes.
Keywords: alkynes; asymmetric catalysis; gold; isomerization; desymmetrization